Religious and Multi-cultural Values in Character-Based English Education - Efendi, Efendi; Budiyono, Bartholomeus (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2019)
The present study portrayed the discourse product When English Rings the Bell presumably containing religious and cultural information as extended values and the teachers’ integration of the information into classroom, manifesting character-based English education herewith. Under quantitative and qualitative descriptive research design, it unfolded religious information to encompass more lexical units of English words (153 events), fewer Indonesian (9), and few non-lexical units of images (65). Meanwhile, multi-cultural information included more lexical units of English words (99 events), fewer Indonesian (40), and few non-lexical units of images (66). Religious values were, then, synthesized from the most occurrences of wearing particular religious clothes (of 58 events). Meanwhile, multi-cultural values were deduced from the utmost events of communicating and being friendly (of 12 events). Outstandingly, the teachers deployed their creativities of teaching-learning media tailored with the problem-, cooperative-, task-, project-, and service-based strategies to foster the students’ English skills. They also suggested the students be creative in their learning to perceive the very religious and multi-cultural information, aimed to alleviate stereotyping cases of certain religious and cultural discourse contents, and promoted peace and unity in Indonesia